Effective advocacy for extension networks: An evaluation of critical capacities - Lamm, Kevan W.; Lamm, Alexa J.; Davis, Kristin E.; Swaroop, B. Jyothi (New Prairie Press, 2018)
Across the globe extension or rural advisory service (RAS) networks are experiencing dramatic changes. Rural to urban population shifts, climate variability, and increased competition for limited resources have created a challenging environment. When done effectively, advocacy is one of the most successful tool extensionists possess to increase understanding and visibility for the value and impacts RAS networks can have. Despite the importance of advocacy there has not been any research into the capacities necessary for RAS networks to advocate effectively. To address the gap researchers conducted a three-round Delphi process with an expert panel of 31 individuals from 24 different countries. The panel achieved consensus on 39 specific capacities necessary for RAS networks to advocate effectively. Additional recommendations are provided for RAS networks to develop capacities accordingly.